2020
DOI: 10.3390/dj8010007
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Healing in Surgically Prepared Bone Defects Using Different Grafting Materials: An Experimental Study in Pigs

Abstract: Regeneration of large jaw bone defects still remains a clinical challenge. To avoid incomplete bone repair, bone grafts have been advocated to support the healing process. This study comparatively evaluated new bone formation among a synthetic graft substitute, a human bone derivative, and a bovine xenograft. Materials were placed in 3 out of the 4 bone cavities, while 1 deficit was left empty, serving as a control, in mono-cortical defects, surgically prepared in the porcine calvaria bone. Animals were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Signs of bone remodeling in defects filled with β-TCP scaffolds were observed in this study and agree with previous studies [7,8]. Recently, Titsinides et al, 2020 [8] compared several grafts, including β-TCP, derived from human bone, and a bovine xenograft, that were grafted into porcine calvaria. Bone formation was more evident in β-TCP at both 8 and 12 weeks by histomorphometric analysis.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Signs of bone remodeling in defects filled with β-TCP scaffolds were observed in this study and agree with previous studies [7,8]. Recently, Titsinides et al, 2020 [8] compared several grafts, including β-TCP, derived from human bone, and a bovine xenograft, that were grafted into porcine calvaria. Bone formation was more evident in β-TCP at both 8 and 12 weeks by histomorphometric analysis.…”
Section: Resultssupporting
confidence: 91%
“…Bone formation was more evident in β-TCP at both 8 and 12 weeks by histomorphometric analysis. However, the results were more relevant at Signs of bone remodeling in defects filled with β-TCP scaffolds were observed in this study and agree with previous studies [7,8]. Recently, Titsinides et al, 2020 [8] compared several grafts, including β-TCP, derived from human bone, and a bovine xenograft, that were grafted into porcine calvaria.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The reduced new bone formation observed after 4 weeks in the DBBM-group compared to the non-augmented control group was in line with previous published data [13]. Using a porcine calvaria defect model, Titsinides et al reported the reduced bone formation in a case of a defect filled with DBBM or β-TCP after 8 and 12 weeks [19]. New bone formed at the expense of β-TCP, which was found to be in the process of degradation, while DBBM remained almost intact.…”
Section: Discussionsupporting
confidence: 89%